Myo-inositol supplementation in gestational diabetes mellitus: is there any interference with diet? - Ahmed, Salma H.; Ibrahim, Ibrahim; Abdullahi, Hala; Khamlaoui, Wided; Samuel, Chinnu George; Badri, Fariada; Ahmad, Fatima; Okunoye, Gbemisola; Terranegra, Annalisa (Frontiers in Nutrition, 2025)
Background/objectivesGestational Diabetes Mellitus (GDM) affects 31.6% of pregnant women in Qatar. Myo-inositol (MI) supplementation has been proposed to reduce GDM risk, but its interaction with diet and lifestyle remains unclear. This study assessed the effects of physical activity and diet on MI supplementation and GDM onset throughout pregnancy.Subjects/methodsA randomized double-blind clinical trial was conducted at Sidra Medicine hospital, involving pregnant women assigned to either the MI (n = 31) or placebo (PLA, n = 33) arm. The Oral Glucose Tolerance Test (OGTT) was conducted between 24 and 28 weeks of gestation. Dietary intake was assessed using 24-h dietary recall and Food Frequency Questionnaires (FFQ), and physical activity and lifestyle data were collected using questionnaires at each trimester. Nutrient analysis was performed using Nutritionist Pro, and dietary patterns were evaluated using the Healthy Eating Index (HEI) and Dietary Inflammatory Index (DII). Statistical analysis was conducted using Prism GraphPad (p ≤ 0.05). ISRCTN Registration number ISRCTN16448440.ResultsDietary adjustments during pregnancy included increased protein and fiber intake, reduced salt, and higher consumption of simple sugars. The MI group showed higher physical activity (walking time/week), lower weight gain, and increased fiber intake (beans and tubers) compared to PLA, which consumed more high-fat, high-sugar foods. Despite these differences, no major differences in GDM incidence were observed between groups.ConclusionMI supplementation was associated with a healthier diet and higher physical activity. Findings suggest that an active lifestyle and balanced diet may enhance MI’s efficacy in lowering GDM risk. Further research is needed to clarify this relationship.Clinical trial registrationThe study Clinical trial registration ID is ISRCTN Registration number ISRCTN16448440.